Farelo de crambe submetido a tratamentos físicos ou químicos para alimentação de ovinos - Moura, Daiane Caroline de (2014)
The process of extraction of crambe oil generates products with high protein content and high potential use in ruminant feed in replacements for traditional sources such as soybeans and cotton. However, the potential presence of glucosinolates (anti-nutritional factor) at high levels is the main limitation to their use in animal feed. Thus, it has developed two experiments to evaluate the effect of different chemical methods (adding CaO at doses of 2, 4 and 6%) and physical (water wash) on the levels of glucosinolates in crambe meal (Experiment 1); and the effects of replacing soybean meal by meal crambe (in natura) not decorticated, or subjected to chemical or physical, on the efficiency of utilization of dietary components in sheep (experiment 2) processing. In experiment 1, 25 samples of 300 grams of bran crambe were distributed in a completely randomized design, with five treatments: control; CaO in doses of 2; 4 e 6%; and washing with water and filtering. The treatment of soybean meal with CaO or crambe by washing with reduced water (P = 0.045) in the levels of glucosinolates average 42.5%. There was no difference (P = 0.236) between alkaline and physical (wash) treatments. The dose of CaO (2, 4 or 6%) did not affect (P = 0.471) the concentration of the compound. The addition of 2% CaO in crambe meal or washing procedure promote only partial reduction of glucosinolates. In experiment 2, eight point 25 ± 2.6 kg body weight wethers were divided into two 4x4 Latin square design with four 15-day period each (10 days of adaptation and five collection), and received four isonitrogenous diets (16% crude protein, dry matter basis, 60% forage and 40% concentrate): control (soybean meal as a protein source); crambe meal as a protein source (22% in the diet, dry matter basis) in the forms in nature (39.7% CP and 56 mg of glucosinolates / kg DM) undergoing treatment with 4% CaO or subjected to washing with water, as described in experiment 1. The replacement of soybean meal by meal crambe did not Affect (p> 0.05) the intake and digestibility of diet components, and the balance of nitrogen (N). The treatment of the white crambe by addition of CaO 4% or by washing with water, though partially reduce the levels of glucosinolates, did not Affect the intake and digestibility of diet components, and the balance of N. Furthermore, the effect of processing method (4% CaO versus wash) on acimas variables mentioned. Thus, white with crambe glucosinolates levels of below 450 mg / kg can be used the the sole source of protein in the diet of ruminants, Replacing soybean meal without the need of physical or chemical procedures for Reducing the anti-nutritional compound.